Vehicle number plate standardization: Assessing towards its non-compliance / Noorliana Suleiman Lee ... [et al.] - Suleiman Lee, Noorliana; Tarudin, Nur Farizan; Mohd Badrillah, Muhammad Izwan; Mohd Nusa, Fatin Najwa; Abdul Latif, Azlin; Mohamed Anuar, Marhani (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
In contemporary times, the acquisition and display of "fancy number plates" have evolved into a source of life satisfaction for specific vehicle owners, particularly when purchasing new vehicles. Consequently, ensuring standardization of number plates has gained significant attention in Malaysia, particularly within the jurisdiction of the Road Transport Department (RTD). The use of non-compliant number plate standards introduces various considerations and can be influenced by an array of factors. Over time, the issue of non-compliance with number plate standardization is poised to become an offense that authorities must address comprehensively to mitigate the misuse of number plates by vehicle owners. This study seeks to identify the variables that influence vehicle owners' decisions to opt for non-compliant number plate standardization in Malaysia. Data for this research was collected through a questionnaire survey distributed across the Kulim, Kedah region. The study identified variables that contribute to the inclination towards non-compliance with number plate standardization. Notably, the research highlights affordability as the most pivotal factor in the selection of a license plate. The findings of this study serve multiple purposes. First and foremost, they offer a valuable reference for the RTD, equipping it to enforce laws pertaining to non-compliance with number plate standardization more effectively. Moreover, the insights gained can lay the groundwork for potential updates to existing regulations, particularly in the Malaysian context. In conclusion, the growing significance of "fancy number plates" as a symbol of personal satisfaction among vehicle owners has led to concerns regarding non-compliance with standardization in Malaysia. By contributing to enhanced law enforcement and policy refinement, this study can aid in better managing the phenomenon of non-compliant number plate standardization in the country.